THE PHENOMENON OF EARLY MARRIAGE AND MARRIAGE POSTPONEMENT IN INDONESIA FROM THE PERSPECTIVE OF MASLAHAH MURSALAH - Ahmad In'am Awaluddin (MADDIKA : Journal of Islamic Family Law, 2025)
This study examines the phenomena of early marriage and delayed marriage in Indonesian society with the aim of identifying the underlying factors and their impacts from the perspective of maslahah mursalah. This study uses a qualitative method with empirical field research. The research subjects consisted of five informants, namely three individuals who married young and two who delayed marriage, while the research objects included the concepts of early marriage and delayed marriage, the driving factors, and the social implications. The results show that the decision to marry young is influenced by economic factors, personal desire, and parental pressure, while the postponement of marriage is influenced by a focus on education and career, not yet finding a suitable partner, and not yet achieving financial stability. This change in marriage patterns is not only an individual choice, but also has an impact on family structure and social construction in society. Early marriage and delayed marriage can be understood as adaptive responses to contemporary social complexities that reflect efforts to achieve maslahah through spiritual considerations, self-development, and readiness to build a quality family life